Drivers don't need to learn all ADAS limitations: A comparison of limitation-focused and responsibility-focused training approaches. (December 2022) - DeGuzman, Chelsea A.; Donmez, Birsen
Highlights: We compared two ADAS training approaches in a remote face-to-face study. We found no difference in ADAS knowledge or reliance intention between approaches. Both training approaches lowered trust for scenarios where ADAS may not work. But training focused on limitations was associated with negative bias towards ADAS. Abstract: Expecting drivers to learn and remember numerous limitations may not be a practical approach to training for advanced driver assistance systems (ADAS), particularly for self-initiated training in the absence of formal training requirements. One alternative is focusing on the importance of the driver remaining engaged in the driving task (responsibility-focused approach). We investigated the effects of two training videos (responsibility-focused and limitation-focused) on reliance intention, trust, and ADAS knowledge. In a remote study, participants (N = 61) watched dashcam clips (8 that require takeover, 8 no takeover) and for each clip, they reported whether they would manually intervene and their trust in ADAS (assessing situational reliance intention and trust, respectively). Participants also completed a questionnaire that included items measuring ADAS knowledge. Responses were collected at three stages: pre-training, post-training, and a follow-up session (minimum four weeks later). There were no significant differences between approaches in terms of knowledge of situations in which ADAS would not work, appropriate situational reliance intention, or trust in takeover scenarios. Compared to the responsibility-focused video, the limitation-focused video was associated with lower trust in no takeover scenarios and negative bias at post-training (i.e., bias towards reporting that ADAS would not work for the knowledge questionnaire and bias towards taking manual control/not using ADAS for the dashcam clips). Given the limited differences between training approaches and potential drawbacks of the limitation-focused approach, our results suggest that the responsibility-focused training approach is worth exploring further.